Dzyadyk formula for summation of double Faber series - Tsvil', M. M. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
An analog of Dzyadyk's formula is constructed for double series in Faber polynomials of two variables. By using this formula, we obtain the estimates of the convergence rate of the double Faber series, summed over rectangles and circles, in a bicylindric domain.